2021
DOI: 10.11591/ijphs.v10i2.20713
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal analysis of dengue hemorrhagic fever in Banyumas, Indonesia

Abstract: Dengue hemorrhagic fever (DHF) is a public health problem in the world and also in Indonesia. One of the districts in Central Java that is still having problems with this disease is Banyumas, Indonesia. The incidence rate (IR) data in 2018 was 2.75 per 100,000 populations and the case fatality rate (CFR) was 3.64%. Spatiotemporal analysis was used to determine local variation, geographic determination of risk zones, and measurement of disease control interventions. Therefore, this study aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Using AHP to combine different variables, the overall model of DHF vulnerability in Gorontalo Regency reveals that the vulnerability area is primarily confined to places with high population density, which is consistent with the findings of the previous study. This finding is consistent with the findings of several studies, which found that DHF risk cases increased in areas with a high population density [1], [28]- [30]. The higher the population of an area will be the greater the potential for female mosquitoes to fly and bite between humans and each other.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Using AHP to combine different variables, the overall model of DHF vulnerability in Gorontalo Regency reveals that the vulnerability area is primarily confined to places with high population density, which is consistent with the findings of the previous study. This finding is consistent with the findings of several studies, which found that DHF risk cases increased in areas with a high population density [1], [28]- [30]. The higher the population of an area will be the greater the potential for female mosquitoes to fly and bite between humans and each other.…”
Section: Discussionsupporting
confidence: 92%
“…Step 3: Establish Priority amongst criteria using pairwise comparison Step 4: Check consistency ratio (CR) using (1) Step 5: Get the relative weights…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies model and analyze the development of diseases [1][2][3][4]. Another type of study in infectious diseases is epidemiology, i.e., the study of the frequency of disease and how the frequency differs across groups of people [5][6][7][8][9][10][11][12]. One of the considerations of epidemiology is to look at the relationships inside the data itself.…”
Section: Introductionmentioning
confidence: 99%